(x+4)(x+7)(x+8)(x+11)+20=0

Simple and best practice solution for (x+4)(x+7)(x+8)(x+11)+20=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)(x+7)(x+8)(x+11)+20=0 equation:


Simplifying
(x + 4)(x + 7)(x + 8)(x + 11) + 20 = 0

Reorder the terms:
(4 + x)(x + 7)(x + 8)(x + 11) + 20 = 0

Reorder the terms:
(4 + x)(7 + x)(x + 8)(x + 11) + 20 = 0

Reorder the terms:
(4 + x)(7 + x)(8 + x)(x + 11) + 20 = 0

Reorder the terms:
(4 + x)(7 + x)(8 + x)(11 + x) + 20 = 0

Multiply (4 + x) * (7 + x)
(4(7 + x) + x(7 + x))(8 + x)(11 + x) + 20 = 0
((7 * 4 + x * 4) + x(7 + x))(8 + x)(11 + x) + 20 = 0
((28 + 4x) + x(7 + x))(8 + x)(11 + x) + 20 = 0
(28 + 4x + (7 * x + x * x))(8 + x)(11 + x) + 20 = 0
(28 + 4x + (7x + x2))(8 + x)(11 + x) + 20 = 0

Combine like terms: 4x + 7x = 11x
(28 + 11x + x2)(8 + x)(11 + x) + 20 = 0

Multiply (28 + 11x + x2) * (8 + x)
(28(8 + x) + 11x * (8 + x) + x2(8 + x))(11 + x) + 20 = 0
((8 * 28 + x * 28) + 11x * (8 + x) + x2(8 + x))(11 + x) + 20 = 0
((224 + 28x) + 11x * (8 + x) + x2(8 + x))(11 + x) + 20 = 0
(224 + 28x + (8 * 11x + x * 11x) + x2(8 + x))(11 + x) + 20 = 0
(224 + 28x + (88x + 11x2) + x2(8 + x))(11 + x) + 20 = 0
(224 + 28x + 88x + 11x2 + (8 * x2 + x * x2))(11 + x) + 20 = 0
(224 + 28x + 88x + 11x2 + (8x2 + x3))(11 + x) + 20 = 0

Combine like terms: 28x + 88x = 116x
(224 + 116x + 11x2 + 8x2 + x3)(11 + x) + 20 = 0

Combine like terms: 11x2 + 8x2 = 19x2
(224 + 116x + 19x2 + x3)(11 + x) + 20 = 0

Multiply (224 + 116x + 19x2 + x3) * (11 + x)
(224(11 + x) + 116x * (11 + x) + 19x2 * (11 + x) + x3(11 + x)) + 20 = 0
((11 * 224 + x * 224) + 116x * (11 + x) + 19x2 * (11 + x) + x3(11 + x)) + 20 = 0
((2464 + 224x) + 116x * (11 + x) + 19x2 * (11 + x) + x3(11 + x)) + 20 = 0
(2464 + 224x + (11 * 116x + x * 116x) + 19x2 * (11 + x) + x3(11 + x)) + 20 = 0
(2464 + 224x + (1276x + 116x2) + 19x2 * (11 + x) + x3(11 + x)) + 20 = 0
(2464 + 224x + 1276x + 116x2 + (11 * 19x2 + x * 19x2) + x3(11 + x)) + 20 = 0
(2464 + 224x + 1276x + 116x2 + (209x2 + 19x3) + x3(11 + x)) + 20 = 0
(2464 + 224x + 1276x + 116x2 + 209x2 + 19x3 + (11 * x3 + x * x3)) + 20 = 0
(2464 + 224x + 1276x + 116x2 + 209x2 + 19x3 + (11x3 + x4)) + 20 = 0

Combine like terms: 224x + 1276x = 1500x
(2464 + 1500x + 116x2 + 209x2 + 19x3 + 11x3 + x4) + 20 = 0

Combine like terms: 116x2 + 209x2 = 325x2
(2464 + 1500x + 325x2 + 19x3 + 11x3 + x4) + 20 = 0

Combine like terms: 19x3 + 11x3 = 30x3
(2464 + 1500x + 325x2 + 30x3 + x4) + 20 = 0

Reorder the terms:
2464 + 20 + 1500x + 325x2 + 30x3 + x4 = 0

Combine like terms: 2464 + 20 = 2484
2484 + 1500x + 325x2 + 30x3 + x4 = 0

Solving
2484 + 1500x + 325x2 + 30x3 + x4 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| -32+4x=-92 | | 1/5+1/3*1/4 | | -21.6+b=-14.7 | | n^3-91n+90=0 | | 73+17=56+x | | 9x=42+3x | | 1-(-26j)=-987 | | 6/x+5/2x=6 | | 5(x-1)=2x+3 | | 115/900 | | -4+10v=36 | | 18-4*3=8*3/4 | | 4(2x+5)=2(4x+10) | | -3x+18=-39 | | 265=z/11-236 | | -0.6x+0.7x+5=-7 | | -0.61-(-7.74)= | | 8+-(3)= | | 6x-1=5x-17 | | -7/8u=-49 | | 6(2y-3)=102 | | z^2+z+17=0 | | 5t+115=570 | | 6(2x-3)=102 | | X+0.08x= | | 2x-3=102 | | 15=-7-a/6 | | -15=-5/3x | | 3s-13s=80 | | X+0.08x=135 | | 15=-7-(a/6) | | 12=-2/5w |

Equations solver categories